ANALISIS TEBAL PERKERASAN LENTUR PADA JALAN TOL AKSES MENUJU BANDARA INTERNATIONAL KERTAJATI - Reynaldi Fransiscus; Sahat Martua Sihombing; Yonas Prima (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Access road to toll road access to Kertajati International Airport, Majalengka Regency, West Java, ispart of the transportation system as a means of service infrastructure for the impact of population growth. Inorder to meet these needs, a new pavement design is needed to serve the traffic needs in the future. The concept offlexible pavement planning is planned for the axle load configuration which results in the greatest stress on theslab. Likewise in the portlan cement association method, the calculations obtained are almost the same as the2017 road pavement design manual (MDP). each obtained for surface AC/WC AC/BC 10.16 cm, Asphalt Base14.85 cm and with a manual design 2017. The resulting AC/WC AC/BC surface layer is 100 cm thick andAsphalt Base is 145 cm thick. So that the total thickness of the flexible pavement is 24.5 cm, from the results ofboth the AC/WC AC/BC surface figures 100 cm Asphalt Base 150 cm, the difference is larger and smaller thanthe calculation. This is due to the basic concept of each method